FORMATION OF PROFESSIONAL COMPETENCES OF FUTURE PHYSICS TEACHERS IN PERFORMING LABORATORY WORK - Khamdamov, Begali (Физико-технологического образование, 2024)
The article considers approaches to changing the structure of laboratory work in physics related to the implementation of Educational Standards. A distinctive feature of the new standard is the formulation of requirements for the results of mastering the main educational programs in the language of competencies, which raises the problem of finding means not only for the formation of competencies, but also for checking the level of their formation. The analysis of textbooks for conducting laboratory work in general physics showed that their structure and content do not fully contribute to the formation of competencies related to future professional activities in the field of teaching methods. The following structure of laboratory work is proposed: setting the goal of the work, control tasks (the goal is to update knowledge), theory of work, control tasks (the goal is to check knowledge of the theory), description of the setup, control tasks (the goal is to check knowledge of the experimental setup), the procedure for performing work with a table for the results of experiments, final control. Among the tasks proposed at the updating stage, a special place is occupied by physical dictations, tasks for establishing analogies, various types of tests. This approach to building the structure of laboratory work in physics contributes to the development of professional competencies in the field of pedagogical activity